(untitled) (Ocean and Coastal Research, 2024)
Magnetic experiments have provided insight into the preservation of magnetite in sediments of the Inner Sea of the Maldives during early diagenesis. In this study, we present high-resolution remanence data on the upper 15 meters of the sedimentary record and a detailed magnetic characterization of discrete samples from the top 5.5 meters of the International Ocean Discovery Program (IODP) Site U1471 record. Based on magnetic experiments, it can be concluded that magnetite is rapidly reduced, with a large decrease in natural remanent magnetization (NRM) related to destruction of primary NRM below the upper two meters of the sedimentary record. In thermomagnetic experiments, the appearance of a greigite signal at 3.06 meters below sea floor (mbsf) suggests that current diagenesis could imprint nearly 100 kry of error on the chronology based on magnetostratigraphy. Furthermore, based on X-ray fluorescence data, it can be concluded that magnetite reduction did not affect the Fe record.